Understanding the origin of photoluminescence in disordered Ca0.60Sr0.40WO4: An experimental and first-principles study - Longo, V. M.; Orhan, E.; Cavalcante, L. S.; Porto, S. L.; Espinosa, J. W. M.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2007)
Visible photoluminescence (PL) was observed for the first time at room temperature in structurally disordered calcium strontium tungstate powder, Ca0.60Sr0.40WO4 (CSW), obtained by the polymeric precursor method. The PL behavior of CSW powders has been analyzed as a function of the disorder rate, based on experimental and theoretical studies. Quantum mechanical theory based on density functional theory at the B3LYP level has been employed to study the electronic structure of two periodic models representing both crystalline and disordered powders. Their electronic structures have been analyzed in terms of density of states, band dispersion and charge densities. The calculations indicate a break in symmetry when passing from crystalline to disordered models, creating localized electronic levels above the valence band. Moreover, a negative charge transfer process takes place from the [WO3] cluster to the [WO4] cluster. The polarization induced by the break in symmetry and the existence of localized levels favors the creation of trapped holes and electrons, originating the PL phenomenon. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: optical materials; Ab initio calculations; photoluminescence; CSW